Characteristics of Entrepreneurs:: An Empirical Analysis - K.R.G. Nair and Anu Pandey (Journal of Entrepreneurship 2006; 15; 47, 2006)
This paper examines the socio-economic and attitudinal characteristics of entrepreneurs on the basis of primary data for the state of Kerala. It does not appear that business acumen runs in families nor is there evidence that religion has an impact on Entrepreneurship. The economic status of the family, age, technical education/training and work experience in a similar or related field seem to favour entrepreneurship. In comparison to the rest of the population, entrepreneurs tend to be more innovative in their attitude, but do not seem to have greater faith in the internal locus of control.